Moralność i religia a rozwój kapitalizmu w ujęciu Deepaka Lala - Matera, Paulina; Matera, Rafał (Annales. Etyka w Życiu Gospodarczym, 2011)
The economist Deepak Lal researches the influence of morality and religion on the shaping of capitalism in different civilizations. His thought was confronted with the remarks of other institutionalists. Lal tries to find out what was the influence of the cost of transactions and the religious beliefs on the evolution of capitalism in chosen countries and regions. Lal claims that materialistic beliefs of agricultural civilizations had not played the key role in the economic growth. The reforms in the Church in the Middle Ages allowed to spread of the instinct of exchange and production of homo oeconomicus. As a result the individualism started to dominate over collectivism. Lal tries to prove that the individualism was not the basis of the Christian faith. The following virtues as: diligence, discipline, frugality, self-help, self-control have had secular origin and nowadays they are more common in India and China than in the West. The Asian civilizations face the dilemma during the economic expansion of the West. They had to choose the path of their development. China and India followed Japan and they modernized without westernization. They tried to find middle course between the tradition and the modernity. We tried to emphasize in the article, that none of the religions have determined the economic fate of the countries. Rather, the morality of the societies and the decision-makers’ beliefs had an influence on economic development.